Plasma MicroRNA-200c as A Prognostic Biomarker for Epithelial Ovarian Cancer - Addin Trirahmanto; Hariyono Winarto; Aria Kekalih; Ferry Sandra (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Ovarian cancer is the 8th most prevalent cancer in women in the world. Current biomarker prognosis for ovarian cancer has numerous limitations, thus new biomarkers are needed. MicroRNAs (miRs) are considered as potential biomarkers in ovarian cancer as they are stable in blood. One candidate is miR-200c, the main regulator in epithelial transition to the mesenchyme. The aim of this study is to determine the role of miR-200c as prognostic biomarker for epithelial ovarian cancer (EOC).METHODS: This is a prospective cohort study conducted at Dr. Sardjito Central General Hospital in Yogyakarta from September 2015 to July 2018. Sampling was done using consecutive sampling method. Forty plasma samples of EOC subjects were included in this study. miR-200c expression was quantified using Reverse Transcriptase Quantitative Quantitative Polymerase Chain Reaction (RTqPCR) with miR-16 as the reference gene.RESULTS: The expression of miR-200c was significantly higher in the group of subjects with preoperative CA-125 levels >500 U/mL (p=0.009) than the group of subjects with preoperative CA-125 levels <500 U/mL. Subjects with higher miR-200c expression had lower survival rate than subjects with lower miR-200c expression, although not statistically significant.CONCLUSION: The miR-200c could be a promising biomarker for EOC. Further studies with larger sample sizes are needed to clarify the prognostic value of miR200c.KEYWORDS: miR-200c, epithelial ovarian cancer, prognosis, overall survival